1991
DOI: 10.1007/bf00731292
|View full text |Cite
|
Sign up to set email alerts
|

Structures of asparagine-linked oligosaccharides from hen egg-yolk antibody (IgY). Occurrence of unusual glucosylated oligo-mannose type oligosaccharides in a mature glycoprotein

Abstract: Asparagine-linked oligosaccharides present on hen egg-yolk immunoglobulin, termed IgY, were liberated from the protein by hydrazinolysis. After N-acetylation, the oligosaccharides were labelled with a UV-absorbing compound, p-aminobenzoic acid ethyl ester (ABEE). The ABEE-derivatized oligosaccharides were fractionated by anion exchange, normal phase and reversed phase HPLC, and their structures were determined by a combination of sugar composition analysis, methylation analysis, negative ion FAB-MS, 500 MHz 1H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(40 citation statements)
references
References 28 publications
2
38
0
Order By: Relevance
“…IgY, the avian homolog of mammalian IgG, was used as a substrate protein because it is one of the few mature secreted proteins that contains an appreciable level of monoglucosylated glycans (ϳ25%) (32). Gel filtration purified IgY was enriched on a calreticulin column (IgY-EN) and used in BLI assays, which revealed the rapid association and dissociation kinetics of the calreticulin-IgY-EN interaction ( Fig.…”
Section: Glycan-dependent and Independent Binding Of Calreticulin To mentioning
confidence: 99%
“…IgY, the avian homolog of mammalian IgG, was used as a substrate protein because it is one of the few mature secreted proteins that contains an appreciable level of monoglucosylated glycans (ϳ25%) (32). Gel filtration purified IgY was enriched on a calreticulin column (IgY-EN) and used in BLI assays, which revealed the rapid association and dissociation kinetics of the calreticulin-IgY-EN interaction ( Fig.…”
Section: Glycan-dependent and Independent Binding Of Calreticulin To mentioning
confidence: 99%
“…It should be pointed out that 61.7% of the high mannose-type glycans in pigeon IgG are mono-glucosylated as found in chicken (serum, egg yolk) (41) and quail (egg yolk) IgGs (43). Specifically, we demonstrated that pigeon IgG-CH3 glycopeptides contain only high mannosetype oligosaccharides.…”
Section: Discussionmentioning
confidence: 57%
“…The data are therefore consistent with the presence of a Glc residue at one of the non-reducing termini of a Man 9 GlcNAc 2 that would block the digestion of the Man residues (later to be shown to be on the ␣3-arm), allowing a removal of only 4 or 5 Man residues from the ␣6-arm. The presence of a monoglucosylated Man 9 GlcNAc 2 along with Man 9 GlcNAc 2 as the major glycoforms has been reported for chicken and quail IgG (41)(42)(43) and may be a characteristic of avian IgG. Further characterization based on two-dimensional HPLC mapping of the PA-derivatives confirmed this structure (see below) and has further resolved Hex 9 HexNAc 2 into Man 9 GlcNAc 2 (n-6, major component) and Glc 1 Man 8 GlcNAc 2 (n-7, minor component), along with Glc 1 Man 9 GlcNAc 2 (n-8), as the predominant high mannose-type structures.…”
Section: Ms and Ms/ms Analysis Of N-glycans From Pigeon Iggmentioning
confidence: 86%
See 1 more Smart Citation
“…2,3 Because carbohydrates lack chromophores, they have been labeled in the past with UV-active or fluorescent [4][5][6][7][8] tags to improve detectability during chromatography. [9][10][11][12][13] The label is most commonly introduced by reductive amination. 14,15 Our group has previously synthesized a prototypical multifunctional small-molecule tag ( Figure 1) for covalent introduction into oligosaccharides which helps to increase the UV sensitivity, separation and isolation of the labeled oligosaccharides.…”
Section: Introductionmentioning
confidence: 99%